2018
DOI: 10.3126/bjhs.v2i3.18937
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Outcome of Antenatal Mothers with Pregnancy Induced Hypertension in Antenatal Ward of Kathmandu Medical College and Teaching Hospital

Abstract: Introduction: Hypertensive disorders seem to complicated in approximately 5-15% of pregnancies. Pregnancy induced hypertension (PIH) increases the risk of maternal and perinatal morbidity and mortality.Objective: To assess the neonatal outcome and to identify the association between the demographic variables and outcome of Pregnancy Induced Hypertension in antenatal ward of Kathmandu Medical College and Teaching Hospital.Methodology: Prospective study design was conducted for the study in Obstetrics ward of Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The same study further reported an APGAR score below 7 among 38.6% of neonate at 5 min, indicating asphyxia. [14][15][16] The study done in Ethiopia [17] showed that still birth, LBW, abortion, preterm birth and low APGAR score were the most neonatal outcomes in mothers with hypertension most common neonatal outcomes disorders. Abortion and preterm delivery were into the proportions of 10.7% and 31.4% respectively.…”
Section: Immediate Parameters and Status Of Neonatesmentioning
confidence: 99%
“…The same study further reported an APGAR score below 7 among 38.6% of neonate at 5 min, indicating asphyxia. [14][15][16] The study done in Ethiopia [17] showed that still birth, LBW, abortion, preterm birth and low APGAR score were the most neonatal outcomes in mothers with hypertension most common neonatal outcomes disorders. Abortion and preterm delivery were into the proportions of 10.7% and 31.4% respectively.…”
Section: Immediate Parameters and Status Of Neonatesmentioning
confidence: 99%
“…In Africa, the situation is complicated, particularly in Low-income countries like those in sub-Saharan Africa, which alone account for 22% of premature births [3]. In the DRC, prematurity accounts for 15% [5] and University Hospital of Kinshasa is 40% [7].…”
Section: Introductionmentioning
confidence: 99%